2019
DOI: 10.1001/jamaneurol.2018.3639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cerebellar Stimulation on Gait and Balance Recovery in Patients With Hemiparetic Stroke

Abstract: IMPORTANCE Gait and balance impairment is associated with poorer functional recovery after stroke. The cerebellum is known to be strongly implicated in the functional reorganization of motor networks in patients with stroke, especially for gait and balance functions. OBJECTIVE To determine whether cerebellar intermittent θ-burst stimulation (CRB-iTBS) can improve balance and gait functions in patients with hemiparesis due to stroke. DESIGN, SETTING, PARTICIPANTS This randomized, double-blind, sham-controlled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
149
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(158 citation statements)
references
References 39 publications
9
149
0
Order By: Relevance
“…The significantly higher compliance in prospective trial registration in the EU CTR registry compared with the rest of the WHO trial registries, might be attributed to the 2014 legal requirements for registration and publication of the results of clinical trials in the European Union, and to the rigor of the registration process in the EU CTR registry 81. In fact, the authors of a publication of a retrospectively registered trial included in our study reported that they were able to register successfully in ClinicalTrials.gov after their initial trial registration was declined at the EU CTR 70. This process might also explain the tendency for European trials not to register in the EU CTR—only 87 of 2086 European trials identified in our study were registered in the EU CTR.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The significantly higher compliance in prospective trial registration in the EU CTR registry compared with the rest of the WHO trial registries, might be attributed to the 2014 legal requirements for registration and publication of the results of clinical trials in the European Union, and to the rigor of the registration process in the EU CTR registry 81. In fact, the authors of a publication of a retrospectively registered trial included in our study reported that they were able to register successfully in ClinicalTrials.gov after their initial trial registration was declined at the EU CTR 70. This process might also explain the tendency for European trials not to register in the EU CTR—only 87 of 2086 European trials identified in our study were registered in the EU CTR.…”
Section: Discussionmentioning
confidence: 83%
“…To investigate the compliance of the submitting authors and the journal editors with the ICMJE recommendations, the full text content of these trials publications was screened and only 2.8% (8/286) of the authors explained the reason for delayed registration of the trial—that is, registering the trial retrospectively after the enrolment of the first participant. Reasons for delayed registration were lack of awareness or error of omission in five papers, that the registration process took longer than anticipated in two papers, and that in one paper the feasibility of recruitment was to be tested before registration 6869707172737475. Appendix M provides details of this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Several questions remain unanswered and could provide novel targets for future studies. For example, several studies have now shown that the effects of iTBS might be even more relevant than those obtained after rTMS [98], and encouraging results have been achieved in the treatment of gait and balance recovery in patients with stroke after cerebellar iTBS [99,100]. Moreover, transcranial alternating current stimulation (tACS) also has recently emerged as a new technique to modulate cortical oscillations and entrain brain rhythms in specific frequencies [101].…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive brain stimulation (NIBS) techniques are increasingly being applied to the cerebellum for various movement disorders, including stroke [1], [2]. In these applications for stroke rehabilitation, improvement in gait and standing balance are the primary goals [3], where NIBS is usually delivered to prime the brain for learning processes by mechanisms of long-term potentiation (LTP) and long-term depression (LTD)-like plasticity [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…In these applications for stroke rehabilitation, improvement in gait and standing balance are the primary goals [3], where NIBS is usually delivered to prime the brain for learning processes by mechanisms of long-term potentiation (LTP) and long-term depression (LTD)-like plasticity [4], [5]. Cerebellar intermittent θ-burst stimulation has been shown to improve balance and gait functions in patients with hemiparesis due to stroke [6] that is important for independent gait without the risk of falling. Another NIBS technique, transcranial direct current stimulation (tDCS), is a low-cost NIBS technique amenable to home-based therapy [7] that applies a small (1-2mA) direct current (DC) via conductive electrodes placed on the scalp [8].…”
Section: Introductionmentioning
confidence: 99%